2008
DOI: 10.1128/jvi.01312-08
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Divergent Strains of Feline Immunodeficiency Virus from the Domestic Cat ( Felis catus ) and the African Lion ( Panthera leo ) Share Usage of CD134 and CXCR4 as Entry Receptors

Abstract: The env open reading frames of African lion (Panthera leo) lentivirus (feline immunodeficiency virus [FIV Ple ]) subtypes B and E from geographically distinct regions of Africa suggest two distinct ancestries, with FIV Ple -E sharing a common ancestor with the domestic cat (Felis catus) lentivirus (FIV Fca) . Here we demonstrate that FIV Ple -E and FIV Fca share the use of CD134 (OX40) and CXCR4 as a primary receptor and coreceptor, respectively, and that both lion CD134 and CXCR4 are functional receptors for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The sequence alignment demonstrates that all 12 CXCR4 residues forming contacts with cholesterol are absolutely, with one exception, conserved across tetrapods including chimpanzee Pan troglodytes and sooty mangabey Cercocebus atys , which are the original sources for HIV‐1 and HIV‐2, respectively 77. Feline CXCR4, but not CCR5, is a coreceptor of FIV (feline immunodeficiency virus) from the domestic cat Felis catus 78 and African lion Panthera leo 79. We found that the 12 residues forming contacts with cholesterol in human CXCR4 are identical to the corresponding residues in CXCR4 orthologs from these two species (Supporting Information Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…The sequence alignment demonstrates that all 12 CXCR4 residues forming contacts with cholesterol are absolutely, with one exception, conserved across tetrapods including chimpanzee Pan troglodytes and sooty mangabey Cercocebus atys , which are the original sources for HIV‐1 and HIV‐2, respectively 77. Feline CXCR4, but not CCR5, is a coreceptor of FIV (feline immunodeficiency virus) from the domestic cat Felis catus 78 and African lion Panthera leo 79. We found that the 12 residues forming contacts with cholesterol in human CXCR4 are identical to the corresponding residues in CXCR4 orthologs from these two species (Supporting Information Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of pol gene sequence of FIV from lions ( Panthera leo ), pumas ( Puma concolor ) and domestic cats indicated that each species has a specific strain of FIV and that the strains are related but distinct [ 7 , 43 ]. Also, strains from African lions (subtype B and E) differ in their abilities to replicate in feline cell lines [ 59 ], their sensitivity to receptor antagonists [ 71 ], and their requirement for ectopic expression of CD134, the primary cellular receptor, for productive infection [ 41 ].…”
Section: Nondomestic Felid Speciesmentioning
confidence: 99%
“…Interestingly, some strains of lion FIV show a substantial divergence in structure and sequence of the envelope receptor binding domains and do not enter via CXCR4 and/or CD134 [ 35 , 36 ]. The cellular receptors for these subtype B lion FIVs have not yet been identified.…”
Section: Entrymentioning
confidence: 99%